2012
DOI: 10.1002/jat.2755
|View full text |Cite
|
Sign up to set email alerts
|

Validation of visualized transgenic zebrafish as a high throughput model to assay bradycardia related cardio toxicity risk candidates

Abstract: Drug-induced QT prolongation usually leads to torsade de pointes (TdP), thus for drugs in the early phase of development this risk should be evaluated. In the present study, we demonstrated a visualized transgenic zebrafish as an in vivo high-throughput model to assay the risk of drug-induced QT prolongation. Zebrafish larvae 48 h post-fertilization expressing green fluorescent protein in myocardium were incubated with compounds reported to induce QT prolongation or block the human ether-a-go-go-related gene (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Interestingly, bradycardia was detected in 4 out of 6 drugs producing QTc prolongation in humans. This is consistent with results presented by Wen et al [57], which showed a correlation between drugs producing QTc prolongation (in dogs) and bradycardia in zebrafish. On the other hand, tachycardia was observed in d -(+)-glucose treated zebrafish larvae.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, bradycardia was detected in 4 out of 6 drugs producing QTc prolongation in humans. This is consistent with results presented by Wen et al [57], which showed a correlation between drugs producing QTc prolongation (in dogs) and bradycardia in zebrafish. On the other hand, tachycardia was observed in d -(+)-glucose treated zebrafish larvae.…”
Section: Discussionsupporting
confidence: 93%
“…This seems certain for ethanol and paracetamol, since their human cardiotoxic impact is observed as a late effect after drug poisoning. In fact, paracetamol has been reported to have no impact on the heart rate in zebrafish larvae [50,57], to the point that Wen et al [54] included this drug as a negative cardiotoxic drug [57]. In summary, we support zebrafish as a powerful tool for predicting drug-induced cardiotoxic liabilities in humans, including typical repolarization and depolarization end-phenotypes such as QTc or EJC.…”
Section: Discussionmentioning
confidence: 54%
“…Testing a new bioactive molecule for hERG safety is mandatory and required by the US FDA. Experimental evaluation of binding affinity to hERG K + channel such as the “gold standard” patch‐clamp electrophysiology,6,7 the in vivo test on zebrafish,8 etc., are laborious, expensive, and time consuming 9. Therefore, there is a need in developing computational tools to reliably identify and filter out potential hERG blockers.…”
Section: Introductionmentioning
confidence: 99%
“…To identify the potential of a substance to delay ventricular repolarization and to estimate the risk for QT interval prolongation in humans, several experiments are conducted. Although new techniques have appeared in the last few years [1113], conventional patch-clamp electrophysiology remains the “gold-standard.” In this test, the electric current passing through hERG channels expressed in cells, is measured [14]. Often, the cell lines utilized as an expression system for the hERG in studies include human embryonic kidney (HEK) 293 cells, Chinese hamster ovary (CHO) cells, or Xenopus laevis oocytes (XO) cells.…”
Section: Introductionmentioning
confidence: 99%